Analysis of Determinants of Mobile Phone Purchasing Decisions in Jakarta Shopping Centers - Muphimin, Muphimin; Nurohmah, Siti (Dinasti International Journal of Digital Business Management, 2024)
This study is to see the effect of digital marketing, brand image, and sales interaction on purchasing decisions mediated by customer satisfaction. This research uses the SEM method using 250 respondents at Mobile Phone Dealers at Shopping Centers in Jakarta. Research results of direct hypothesis testing show that Digital Marketing has a significant effect on Sales Performance, but not on Customer Satisfaction. Brand Image has a significant effect on Customer Satisfaction and almost significant on Sales Performance. Sales Interaction has a significant effect on Sales Performance and Customer Satisfaction. Customer Satisfaction has a very significant effect on Sales Performance. Indirect Hypothesis shows that the relationship between Digital Marketing, Customer Satisfaction, and Sales Performance is not significant. However, Brand Image and Sales Interaction have a highly significant effect on Sales Performance through Customer Satisfaction. The research concludes that Digital Marketing affects Sales Performance, while Brand Image and Sales Interaction affect Sales Performance and Customer Satisfaction. Customer Satisfaction has an effect on Sales Performance.